PENINGKATAN HASIL BELAJAR IPS MELALUI PENGGUNAAN MEDIA GAMBAR PADA SISWA KELAS III SDN 50 BULU DATU PALOPO - Dahlia, Dahlia (Pedagogik Journal of Islamic Elementary School, 2019)
The main problem in this study is the low learning outcomes of social studies for III grade students of SDN 50 Bulu Datu Palopo . There is also the problem formulation, that is : can the purpose of this study is that student learning outcomes can be improved by using picture media in class III SDN 50 Bulu DATU Palopo on subject IPS. held three times, with the planning stage act of observation and reflection. The subject of this research is class students III SDN 50 Bulu Datu Palopoin odd semester of school year 2018/2019 with a total of 23 students . The results of the show that : with the use of media images off class IIIÂ  SDN 50 Bulu Datu Palopo students learning outcomes conducted in two cycles shows that student learning outcomes have increased,from the cycle I average value 72 with percentage of completeness 65%, while cycle II average value 92 with percentage of complete 100% and has fulfilled the value KKM that is 70.